A Conceptual Study of Upanaha Swedana (AYUSHDHARA, 2021)
Swedana Karma is undertaken by inducing sweating from the application of heat. There are many methods used to achieve this, with Upanaha Swedana being one of them. Upanaha Swedana is a standard treatment modality used in Ayurveda for the management of pain and inflammation. It is a localized treatment wherein a combination of medicinal drugs are prepared, made into a poultice, heated and applied at the affected site. This is meant to reduce the local inflammation and act as a topical analgesic. The procedure is divided into three phases which are: Purva Karma (pre-therapy procedures), the preparation of the Upanaha Swedana material is done, Pradhana Karma (main therapeutic procedures) the prepared Upanaha Swedana material is applied to the patient and Paschat Karma (post-therapy procedures) after waiting the specified times, the Upahana Swedana is removed following proper procedures. The present conceptual study was done based on the need of the day to elaborate the process of conducting Upanaha Swedana. For this, various Ayurvedic texts, digital libraries referencing Samhita were searched and the following headings were selected, types of data, types of reports and functionalities. This article seeks to explore this treatment modality and outline the general approach to be followed while conducting the procedure of Upanaha Swedana.